Retrospektywna refleksja nad „porażką” w świadomości społecznej narodów Europy Środkowo-Wschodniej .......... 165 - Kornijewskyj, Ołeksandr; Fyłypenko, Artem (Tożsamość i pamięć : konteksty kulturowe i społeczne. Studia ukrainoznawcze, 2021)
RETROSPECTIVE REFLECTION ON “FAILURE” IN THE SOCIAL AWARENESS OF THE NATIONS OF CENTRAL AND EASTERN EUROPEThe research of the public perception of the collapse of the Soviet Union in the two largest post-soviet states – Ukraine and the Russian Federation – prove that among the Russian people the post-imperial syndrome and revanchist sentiments prevail, officially supported and encouraged by the Russian government. The authors explore the controversial processes of the evolution of historical conscience in Romania and Moldova, as well as the current policy of Hungary toward Hungarian communities in other countries, including in Ukraine.